Koleksi Mebel Antik Museum Sejarah Jakarta - Amarena Nediari (Bina Nusantara University, 2010)
Collection of antique furniture is the most dominant type collection belongs to the Jakarta History Museum. The museum building is located in tourist areas Kotatua Jakarta, which became the center of historic and cultural development of the city. The purpose of this research is to determine the condition of furniture in the museum's collections so that the rescue of cultural heritage and history associated with the city through the exhibition can be done well. Methods of research conducted by collecting data from various literature sources, surveys and interviews with the management of Jakarta History Museum as a resource. Unfortunately, the furniture collection is currently not maintained and not well protected so that the high historical value of cultural heritage and history of the city of Jakarta is almost negligible. Conclusion from this research is to realign of the furniture collection at the Museum of History of Jakarta.